Mitigation in Disasters Role of Royal Nepal Army and Shree Birendra Hospital - Rayamajhi, K N (Medical Journal of Shree Birendra Hospital, 1999)
Mitigation in Disasters Role of Royal Nepal Army and Shree Birendra Hospital